Life Experiences of Patients Suffering end Stage Renal Disease - Yulis Setiya Dewi; Harmayetti Harmayetti; Ninuk Dian Kurniawati; Erna Dwi Wahyuni; Deni Yasmara; Abu Bakar; Sukma Randani I (Universitas Airlangga, 2013)
Introduction: Haemodialysis (HD) is one of therapies to sustain life for people with End Stage Renal Disease (ESRD). HD and ESRD are the source of the stressor for the patients. The purpose of this study was to gain insight about the life experiences of patients suffering from ESRD and coping that they used in dealing with stressors.Methods: This study employed hermeneutic phenomenological study as methodology. Samples were taken at RSU Dr. Soedono Madiun in December 2010–May 2011 using purposive sampling. Participants in this study amounted to 9 people who all male and had suffered kidney failure and undergoing HD for more than 2 years. Data were processed and analysed through the nine stages data interpretation according collaizi.Results: Client's life experiences with HD and coping strategies they used to cope with critical situations have been identified and grouped into several themes. The first theme was the reaction of participants when receiving the diagnosis should undergo HD including: sad, rejection, fear, shock and feelings of resignation and hope. The second theme was perceived to critical situations by clients include shortness of breath, weakness, body swelling, itching, diarrhea and could not urinate. Last theme was the meaning of life in hemodialysis derived from attitudinal values (the values to be) and experiential values (the values of appreciation).Conclusion: Ways in which clients address critical situations were quite diverse. Emotional informational, instrumental supports from spouse or significant other were needed by participants to overcome the critical situation. This study suggests that nurse should perform therapeutic communication to HD patients so that patients may cope with the disease more positively.